Controlled freezing inactivates Trichinella britovi in wild boar meat: Insights from a murine infection model and multiplex polymerase chain reaction - Olimpia C. Iacob; Aurelian-Sorin Pașca; Laura Andree Olariu; Larisa Maria Ivănescu; Mihai Mareș (Veterinary World)
Background and Aim: Trichinellosis remains a public health concern globally due to the zoonotic potential of consuming undercooked meat infected with Trichinella spp. larvae. Trichinella britovi, known for its moderate freeze tolerance, presents a food safety challenge, particularly in game meat such as wild boar. This study aimed to evaluate the infectivity of T. britovi larvae in wild boar meat subjected to prolonged freezing under controlled conditions.